The effect of unplanned extubation (UPE) bundle on extubation incidence in critically ill children In Pediatric Intensif Care Unit (PICU) Central General Hospital of dr. Kariadi Semarang - Umi Yanti Maisaroh; Setyoningsih Setyoningsih; Silvy Andriyani; Yayuk Setyowati; Lilik Eko Sunarto (Media Keperawatan Indonesia)
The Pediatric Intensive Care Unit (PICU) is a separate unit to handle pediatric patients with medical, surgical, and trauma disorders or life-threatening conditions. Endotracheal intubation is a common invasive procedure in pediatric intensive care. Unplanned extubation occurs when the endotracheal tube is accidentally removed. In January 2022, the Intensive Care Installation (IRIN) determined the occurrence of unplanned extubation (UPE) in selected quality indicators. These results require further study to determine the internal factors that influence the occurrence and effect of implementing a bundle on the occurrence of unplanned extubation (UPE) in the PICU (pediatric intensive care unit). This study was to determine the effect of the unplanned extubation (UPE) bundle on reducing the incidence of extubation in critical pediatric patients in the Pediatric Intensive Care Unit (PICU). The method was a quasi-experimental intervention with control and intervention groups containing the unplanned extubation (UPE) bundle, with a total of 20 samples of control and intervention. Inclusion criteria: patients aged <6 years who had an endotracheal tube (ET) with and without ventilator support (T-piece, Jackson-Reese) who were treated in the PICU of Dr. Kariadi General Hospital, Semarang. Data analysis using univariate, bivariate (chi-square), and multivariate (multiple linear regression) methods. The conclusion is that there was an influence of assessment variables of the Unplanned Extubation (UPE) bundle and internal factors of hypersalivation and psychomotor agitation in the occurrence of Unplanned Extubation (UPE) with a p-value of 0.00<0.05 and a value of f count of 10.193>3.01. Research recommendations can be standard operating procedures in pediatric intensive care to improve the quality of nursing services by reducing the incidence of unplanned extubation (UPE).